Teknologi Realitas Virtual (RV) dalam Pelatihan Bahasa Asing untuk Pelaku UMKM Indonesia - Iis Kurnia Nurhayati; Yulia Nur Hasanah; Nia Kurniasih; Fathah Noor Prawita (Fakultas Seni Rupa dan Desain ITB, 2023)
This article evaluates the integration of virtual reality (VR) technology in foreign language training for SMEs in Indonesia using the Kirkpatrick Model. The study involved SME actors from various industries who participated in a tailored VR language training program. Surveys and interviews were conducted to assess participants' reactions, perceptions, and relevance to language learning goals. The evaluation measured learning outcomes such as improved language proficiency and increased confidence in using foreign languages in business settings. The study also investigated behavioral changes resulting from VR training, including language skills application in daily business activities and communication strategies with international partners or customers. The overall impact of the program on SMEs' competitiveness, market expansion, and international collaboration was evaluated. The findings indicate that the VR training program was effective, with positive reactions, learning outcomes, and behavioral changes in business activities. The study emphasizes the importance of measuring reactions and suggesting improvements in training materials and implementation schedules based on participant feedback. The VR-based language training program holds promise for enhancing SMEs' language skills, competitiveness, and internationalization efforts.